"A Hook Fast in His Heart": Emotion and "True Christian Knowledge" in Disputes over Conversion between Lutheran and Moravian Missionaries in Early Colonial Greenland2. (25th June 2015) - McLisky, Claire
Abstract : This article explores the role of emotion in Christian conversion for Lutheran and Moravian missionaries to early colonial Greenland. As self‐appointed agents of emotional change, both Lutherans and Moravians attempted to transform the emotional worlds of Indigenous peoples in Greenland, before, during and after their conversion to Christianity, and in some senses they can be said to have been successful. Yet their control over Indigenous emotional expression was never complete, and differences between the two denominations could, at times, be used by Greenlanders to assert their own political, spiritual, and emotional agency.